APPLICATION OF THE PROJECT BASED LEARNING MODEL TO IMPROVE PHYSICAL SPORT AND HEALTHY EDUCATION LEARNING OUTCOMES FOR VOCATIONAL HIGH SCHOOL STUDENT HOSPITALITY VOLLEYBALL MATERIAL - Simatupang, Hani Elinta Br; Mashuri, Hendra; Dartini, Ni Putu Dwi Sucita (STKIP Citra Bakti, 2024)
This research aims to determine the improvement in physical sport and healthy education learning outcomes through volleyball material for class XI Hospitality students at Vocational High School 1 Singaraja by applying the Project Based Learning learning model. This research is a type of classroom action research. The subjects of this research were students in class XI Hospitality at Vocational High School 1 Singaraja, totaling 37 students. Data was collected by means of written tests and practical tests on basic upper passing and lower passing techniques using the format of assessing basic upper passing and lower passing techniques on cognitive aspects, psychomotor aspects and affective aspects. Data was analyzed using Descriptive Statistics analysis. The results of the research show that there has been an increase in the learning outcomes of physical sport and healthy education volleyball material for students using project based learning which can be seen from the increase in the average learning outcomes from cycle I from 71.4 to 86.3 in cycle II, with the previous learning being complete in cycle I 12 (32.43%) people increased to 37 (100%) people in cycle II. So the Project Based Learning model can improve physical sport and healthy education learning outcomes in volleyball material for Class XI Hospitality students. For this reason, it is recommended for teachers to choose the Project based learning (PjBL) learning model in their classroom action research if they want to overcome the problem of learning outcomes and student activity.